Formação de professores de Ciências Naturais em uma perspectiva interdisciplinar e crítica : reflexões sobre a contribuição da vivência com questões sociocientíficas na mobilização e aprendizagem de conhecimentos para a docência - Ribeiro, Kátia Dias Ferreira (2016)
In this research the objective was to investigate the processes of mobilization and learning of knowledge for teaching, aiming for the training in an interdisciplinary and critical perspective, by future teachers of Natural Sciences during a training action with socio-scientific issue approach. In 40h of activities, the use of pesticides in soybean production in the north of the state of Mato Grosso was studied and discussed, a subject that is part of the experiential reality of the participants. Studies on teacher training and, in particular, the training of Natural Sciences teachers, knowledge for teaching and socio-scientific issues contributed to the construction of the theoretical framework and served as mentors for analysis. 20 students of the Licenciatura em Ciências Naturais e Matemática course (LCNM) (Degree in Natural Sciences and Mathematics) of Universidade Federal de Mato Grosso (UFMT), campus of Sinop (CUS), participated in the activities. For the development of the formative action, TV reports, articles in informative newspapers, Internet videos, scientific and popular science papers were used to present different actors and understandings on the subject, the use of pesticides. Semistructured interview, reflective diary, matrices, and audio and video recordings were the instruments used for obtaining information and subsequent construction of data. The Content Analysis (CA) was appropriated to, having the records as basis, constitute the corpus of analysis and undertake the development of an interpretation of the phenomenon. In the data analysis, aspects to be considered were settled, using as basis the objectives and research questions based on the categories of knowledge for teaching explored in this research: knowledge of content, didactic and pedagogical knowledge and critical knowledge. The analyses were performed while minding the construction and acquisition of knowledge aiming a training through an interdisciplinary and critical perspective. In this sense, the ideas of overcoming of individualism of the subject and the knowledge and citizen action in society to promotion of changes are explicit, ideas that emerge from the formative pretensions to the teacher of Natural Sciences and theoretical frameworks used. The results indicate that the learning of knowledge for teaching occurs in the involvement of socioscientific issues analysis providing elements that help in the reflection on possibilities of contemplate a training of Science teachers in an interdisciplinary and critical perspective. Moreover, it was possible to identify weaknesses in the education and training needs that need to be considered and overcomed.